HBIW hydrogenolysis debenzylation catalyst, preparation method and application
By loading palladium nanoparticles onto titanate nanotubes, the HBIW hydrogen debenzylase catalyst solved the problems of high loading and poor stability of Pd/C catalysts, enabling efficient recycling of the catalyst and large-scale production of CL-20.
Patent Information
- Application Number
- CN202511264842.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-05
- Publication Date
- 2025-11-28
AI Technical Summary
In existing HBIW debenzyl hydrodehydrogenase catalysts, the high loading of Pd/C catalysts and their poor stability lead to easy deactivation of the catalysts, which limits the large-scale production of CL-20.
Using titanate nanotubes as a support, palladium nanoparticles with an average particle size of 1-5 nm were loaded by atomic layer deposition to form strong covalent bonds (Pd-O-Ti), thus preparing the HBIW hydrogen debenzylase catalyst.
The stability and activity of the catalyst were improved, the palladium loss rate was less than 9 wt%, and the TADBIW yield decreased by ≤10%, enabling the recycling of the catalyst and the large-scale production of CL-20.
Smart Images

Figure CN121016736A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of catalysts, and relates to a palladium catalyst, in particular to an HBIW hydrogenolysis debenzylization catalyst, a preparation method and application thereof. BACKGROUND
[0002] Hexabenzylhexaazaisowurtzitane (HBIW) is an important precursor for synthesizing CL-20, which can be prepared by condensation of benzylamine or substituted benzylamine with glyoxal. HBIW undergoes the first hydrogenolysis reaction under the action of a Pd / C catalyst, that is, four benzyl groups connected with the cage structure are removed, C-N chemical bond is broken, and tetraacetyldibenzylhexaazaisowurtzitane (TADBIW) is obtained. Since the cage structure of HBIW is unstable, the hydrogenolysis reaction can only be carried out at a mild reaction temperature. The Pd / C catalyst has good catalytic activity and selectivity at a low temperature, and is a commonly used catalyst for the HBIW hydrogenolysis debenzylization reaction.
[0003] At present, the Pd / C catalyst used for synthesizing CL-20 has a high loading of noble metal Pd of 5-20 wt%. The noble metal Pd-based catalyst with such a high loading can only make the CL-20 hydrogenolysis debenzylization reaction proceed normally. In addition, the Pd / C catalyst has poor stability, and Pd particles on the surface of the carrier will migrate during the hydrogenolysis reaction, thereby causing agglomeration and loss, causing catalyst deactivation, low repeated utilization rate, and thus limiting the large-scale production of CL-20.
[0004] To reduce the amount of Pd and improve the activity of the catalyst, researchers prepared Pd / AC (Propellants, Explosives, Pyrotechnics 2017, 42, 213-219), Pd / carbon nanotube (Central European Journal of Energetic Materials 2015, 12, 439-458), Pd / flower carbon (Catalysts 2021, 11, 441), Pd / cellulose (Catalysts 2023, 13, 637), Pd / C3N4 (Chemistry Select 2022, 7, e202104216; Applied Catalysis A: General 2021, 624, 118310) catalysts by co-precipitation method, sol-gel method, ion exchange method and co-emulsion method. The carbon material as the carrier has a three-dimensional structure carbon-based carrier that can better disperse Pd nanoparticles, but the interaction between Pd and the carbon-based carrier is weak, which leads to the separation of part of Pd from the carrier during the reaction; the metal oxide TiO2, Al2O3 and SiO2 as the carrier (ACS Applied Nano Materials 2020, 4, 159-166; Molecular Catalysis 2019, 477, 110556; Catalysis Communications 2018, 109, 28-32) can prepare Pd nanoparticles with an average particle size of 2-3 nm and strong interaction with Pd, but the low specific surface area is not conducive to the adsorption and diffusion of HBIW macromolecular reactant molecules, which reduces the reaction efficiency, and in addition, the oxide without mesoporous channels does not limit the aggregation of Pd particles, which leads to the decrease in activity or even deactivation of the catalyst after single use. SUMMARY
[0005] In view of the deficiencies in the prior art, the purpose of the present application is to provide an HBIW hydrogenolysis debenzylization catalyst, a preparation method and an application, which solves the technical problem that the catalytic performance of the HBIW hydrogenolysis debenzylization catalyst in the prior art needs to be further improved.
[0006] To solve the above technical problems, the technical scheme is adopted as follows: An HBIW hydrogenolysis debenzylization catalyst, which comprises a titanium nanotube as a carrier and active substance Pd loaded on the carrier; the active substance Pd is a nanoparticle with an average particle size of 1-5 nm; and the loading amount of the active substance Pd is 2.5wt%-7.8wt%.
[0007] The present application also has the following technical features: The application also protects a preparation method of the HBIW hydrogenolysis debenzylization catalyst as described above, which is synthesized by using the atomic layer deposition method in a rotating reactor, taking the titanate nanotube as the carrier, taking the palladium hexafluoroacetylacetone as the precursor, and taking the formaldehyde as the precursor, and the titanate nanotube loaded palladium catalyst is the HBIW hydrogenolysis debenzylization catalyst.
[0008] Specifically, the method vacuums the cavity of the rotating reactor to control the pressure at 100-200 Pa, heats the rotating reactor to 150-200 ℃, preheats the palladium hexafluoroacetylacetone precursor to 50-60 ℃, and the flow rate of the inert carrier gas is 100-200 ml / min, and then the atomic layer deposition method is used to deposit 1-3 cycles of the active substance palladium on the titanate nanotube.
[0009] Preferably, the method vacuums the cavity of the rotating reactor to control the pressure at 130 Pa, heats the rotating reactor to 200 ℃, preheats the palladium hexafluoroacetylacetone precursor to 60 ℃, and the flow rate of the inert carrier gas is 100 ml / min.
[0010] Specifically, one cycle of the atomic layer deposition method includes the following four steps: Step one, inject the palladium hexafluoroacetylacetone precursor to make it have a surface interface chemical reaction with the titanate nanotube, and the injection time of the palladium hexafluoroacetylacetone precursor is 100-2000 seconds.
[0011] Step two, the inert carrier gas is purged for 200-1000 seconds.
[0012] Step three, inject the formaldehyde precursor to reduce the palladium hexafluoroacetylacetone on the surface, and the injection time of the formaldehyde precursor is 150-3000 seconds.
[0013] Step four, the inert carrier gas is purged for 200-1000 seconds.
[0014] Preferably, one cycle of the atomic layer deposition method includes the following four steps: Step one, inject the palladium hexafluoroacetylacetone precursor to make it have a surface interface chemical reaction with the titanate nanotube, and the injection time of the palladium hexafluoroacetylacetone precursor is 200-1000 seconds.
[0015] Step two, the inert carrier gas is purged for 200-1000 seconds.
[0016] Step three, inject the formaldehyde precursor to reduce the palladium hexafluoroacetylacetone on the surface, and the injection time of the formaldehyde precursor is 300-1500 seconds.
[0017] Step four, the inert carrier gas is purged for 200-1000 seconds.
[0018] The optimal atomic layer deposition (ALD) cycle comprises the following four steps: Step 1: Inject palladium hexafluoroacetylacetonate precursor to induce an interfacial chemical reaction with titanate nanotubes. The injection time of palladium hexafluoroacetylacetonate precursor is 300 seconds.
[0019] Step 2: Purge with inert carrier gas for 500 seconds.
[0020] Step 3: Inject palladium hexafluoroacetylacetonate onto the surface of the formaldehyde precursor. The formaldehyde precursor injection time is 600 seconds.
[0021] Step 4: Purge with inert carrier gas for 500 seconds.
[0022] This invention also protects the application of the HBIW hydrodebenzylation catalyst described above in the primary HBIW hydrodebenzylation reaction. The decrease in TADBIW yield after the HBIW hydrodebenzylation catalyst is recycled three times is [not specified in the original text]. ≤10%; after the HBIW hydrogen debenzyl catalyst is recycled 3 times, the loss rate of active material palladium is ≤20wt%.
[0023] Preferably, after the HBIW hydrodebenzyl catalyst is recycled three times, the decrease rate of TADBIW yield is [not specified]. ≤6.9%; after the HBIW hydrodebenzyl catalyst is recycled 3 times, the loss rate of active material palladium is ≤9wt%.
[0024] The amount of palladium, the active material, in the titanate nanotube-supported sub-nanometer palladium catalyst is 5.0 wt‰ to 15.6 wt‰ of the hexabenzylhexaazaisowulzane.
[0025] Preferably, the reaction temperature for the HBIW primary hydrogen debenzylation reaction is 20°C to 40°C.
[0026] Preferably, the yield of TADBIW is 80.4% to 87.2%.
[0027] Compared with the prior art, the present invention has the following technical effects: (I) In this invention, palladium (Pd) nanoparticles are deposited on a titanate nanotube (H2Ti3O7) support by atomic layer deposition. The mesoporous structure (pore size 5-15nm) of titanate nanotubes can eliminate internal diffusion and accelerate the mass transfer of reaction substrates.
[0028] (II) The hydroxyl groups naturally formed on the surface of the titanate nanotubes of the present invention form strong covalent bonds (Pd-O-Ti) with palladium, which can inhibit migration, aggregation and loss of active material palladium. After the catalyst is recycled 3 times, the loss rate of active material palladium (Pd loss amount / initial Pd amount) can be less than 9 wt%, and the TADBIW yield decreases by ≤10%.
[0029] (III) The rotary reactor used in this invention can prepare catalysts in batches, further reducing catalyst costs and making it easy to achieve large-scale production of CL-20. Attached Figure Description
[0030] Figure 1 The N2 adsorption-desorption curves and pore size distribution curves of Pd / H2Ti3O7 catalysts with different period numbers are shown.
[0031] Figure 2 XRD patterns of Pd / H2Ti3O7 catalysts with different period numbers.
[0032] Figure 3 XPS spectra of Pd / H2Ti3O7 catalysts with different period numbers.
[0033] Figure 4 The images are TEM images of different catalysts, where (a1, a2) are TEM images of commercial 5wt% Pd / C, (b1, b2) are TEM images of 1cPd / H2Ti3O7, (c1, c2) are TEM images of 2cPd / H2Ti3O7, and (d1, d2) are TEM images of 3cPd / H2Ti3O7.
[0034] Figure 5 The images show STEM and EDSMapping diagrams of the 1cPd / H2Ti3O7 catalyst, where yellow represents Pd, green represents Ti, and blue represents O.
[0035] Figure 6 The images show STEM and EDSMapping diagrams of the 2cPd / H2Ti3O7 catalyst, where yellow represents Pd, green represents Ti, and blue represents O.
[0036] Figure 7 The XRD patterns of the 1cPd / H2Ti3O7spent1, 2cPd / H2Ti3O7spent1, and 3cPd / H2Ti3O7spent1 catalysts recovered after one cycle of use are shown.
[0037] Figure 8These are TEM images of the catalyst recovered after one cycle of use. Among them, (a) is a commercial 5 wt% Pd / Cspent1, (b) is a 1 cPd / H2Ti3O7spent1, (c) is a 2 cPd / H2Ti3O7spent1, and (d) is a 3 cPd / H2Ti3O7spent1.
[0038] Figure 9 This is a STEM image of the 1cPd / P25spent1 catalyst recovered after one cycle of use.
[0039] Figure 10 XPS spectra of the 1cPd / H2Ti3O7spent1, 2cPd / H2Ti3O7spent1, and 3cPd / H2Ti3O7spent1 catalysts recovered after one cycle.
[0040] The specific content of the present invention will be further explained in detail below with reference to the embodiments. Detailed Implementation
[0041] It should be noted that all materials and equipment used in this invention, unless otherwise specified, are those known in the art. For example, the rotary reactor is a rotary reactor known in the art.
[0042] Atomic layer deposition (ALD) surface technology enables the precise synthesis of nanoscale Pd-based catalysts. To address the problems with the supports described in the background art, this invention employs titanate nanotubes (H₂Ti₃O₇) as the Pd catalyst support. The mesoporous structure (pore size 5–15 nm) of titanate nanotubes eliminates internal diffusion, accelerates substrate mass transfer, and the naturally formed hydroxyl groups on their surface form strong covalent bonds with Pd (Pd-O-Ti), inhibiting migration and aggregation.
[0043] The following are specific embodiments of the present invention. It should be noted that the present invention is not limited to the following specific embodiments. All equivalent modifications made based on the technical solutions of this application fall within the protection scope of the present invention.
[0044] Example 1: This embodiment provides a method for preparing an HBIW hydrogen debenzylase catalyst, which includes the following steps: First, the catalyst support titanate nanotubes are placed in a rotary reactor, the reactor is sealed, a vacuum is drawn to control the chamber pressure at 130 Pa, the temperature is heated to 200 °C, the hexafluoroacetylacetone palladium precursor is preheated to 60 °C, the flow rate of inert carrier gas nitrogen is 100 ml / min, and then the active material palladium is deposited on the titanate nanotubes.
[0045] One cycle of atomic layer deposition consists of four steps: Step 1: Inject palladium hexafluoroacetylacetone precursor into the rotary reactor to induce an interfacial chemical reaction with titanate nanotubes. The injection time is 300 seconds.
[0046] Step 2: Purge with inert carrier gas nitrogen for 500 seconds.
[0047] Step 3: Inject formaldehyde precursor into the reactor to reduce the palladium hexafluoroacetylacetonate on the surface to generate palladium particles. The injection time is 600 seconds.
[0048] Step 4: Purge with inert carrier gas nitrogen for 500 seconds.
[0049] The atomic layer deposition period numbers of Pd are 1, 2 and 3, and the catalysts are denoted as 1cPd / H2Ti3O7, 2cPd / H2Ti3O7 and 3cPd / H2Ti3O7.
[0050] The 1cPd / H2Ti3O7, 2cPd / H2Ti3O7 and 3cPd / H2Ti3O7 catalysts were characterized by BET, XRD, XPS and TEM.
[0051] Figure 1 These are the N2 adsorption-desorption curves and pore size distribution curves of Pd / H2Ti3O7 catalysts with different ALD period numbers. Figure 1 As shown in (a), the 1cPd / H2Ti3O7, 2cPd / H2Ti3O7 and 3cPd / H2Ti3O7 catalysts all have hysteresis loops of the same size, indicating that Pd in the 1 to 3 cycles did not block the channels and the catalysts still maintained a mesoporous structure. Figure 1 (b) shows that the average pore size is 11 nm after 1 to 3 cycles of Pd deposition on the H2Ti3O7 support.
[0052] Table 1 lists the test results of Pd content and pore structure in Pd / H2Ti3O7 catalysts with different ALD period numbers and Pd.
[0053] Table 1. Pd content and pore structure results of Pd / H2Ti3O7 catalysts with different ALD cycle numbers.
[0054] Table 1 shows that the Pd content in the 1–3 cPd / H2Ti3O7 catalysts is 2.5 wt%, 4.3 wt%, and 7.8 wt%, respectively. The Pd content increases almost linearly with the increase of the Pd cycle number. After one cycle of Pd deposition on the H2Ti3O7 support, the specific surface area increases from 274 m² / s². 2 / g decreased to 220m 2 / g indicates that Pd is deposited inside the titanate nanotubes. After two Pd deposition cycles, the specific surface area actually increases to 262m². 2 / g, possibly because there was still Pd that was not completely reduced in the first cycle, and the ligands were removed after reduction in the second cycle. The specific surface area of the catalyst after three cycles of Pd deposition decreased to 224m². 2 / g. After 1–3 cycles of Pd deposition, the pore size of the H₂Ti₃O₇ support increased from 11.3 nm to approximately 11.7, 11.5, and 11.7 nm, possibly around 200 nm. 0 C deposition temperature causes shrinkage of the multilayer walls of titanate nanotubes, resulting in a reduction in pore size.
[0055] The phase structures of the H2Ti3O7 support and the 1–3cPd / H2Ti3O7 catalysts were characterized by XRD, and the results are as follows: Figure 2 As shown. The support H2Ti3O7 at 2θ = 24.5 0 48.6 0 The presence of diffraction peaks of titanate at the deposition site, and the absence of Pd diffraction peaks after deposition of Pd with different number of periods, indicates that Pd nanoparticles are highly dispersed on titanate nanotubes.
[0056] The electronic structure of the catalyst was analyzed by XPS, and the results are as follows: Figure 3 As shown, peak fitting was performed on the Pd 3d spectrum of the 1cPd / H2Ti3O7 catalyst, and the peak with a binding energy of 335.5 eV was attributed to elemental metal Pd. 0 The binding energy of 336.8 eV is attributed to the oxidation state of Pd. 2+ 337.3 eV and 338.6 eV are attributed to the oxidation state of Pd. n+ peak (n>2) Figure 3 (a) As the number of ALD periods of deposited Pd increases to 2, the metallic Pd... 0 The peak area of the spectrum gradually increases, indicating that the oxidation state of Pd is increasing. n+ The peak area of the spectrum decreases accordingly. During the third period, the reduction depth increases, and more oxidized Pd... n+ Reduced to metallic Pd ( Figure 3 (b~c in the middle). Figure 3 In the image, d represents the Ti2p spectrum of the 1–3cPd / H2Ti3O7 catalyst, and the peak with a binding energy of 458.6 eV is attributed to Ti. 4+ .
[0057] Figure 4 These are TEM and HRTEM images of commercially available 5wt% Pd / C and 1–3cPd / H₂Ti₃O₇ catalysts. From Figure 4 As can be seen from a1 to a2, the average particle size of the Pd nanoparticles loaded on the activated carbon is 3.8 nm, and the particle size distribution is uneven. Figure 4Images b1–d2 show high- and low-magnification transmission electron microscopy (TEM) images of the 1–3cPd / H2Ti3O7 catalysts, revealing that the H2Ti3O7 morphology is a nanotube structure with open ends. The average particle sizes of Pd particles in the 1cPd / H2Ti3O7, 2cPd / H2Ti3O7, and 3cPd / H2Ti3O7 catalysts are 4.3 nm, 3.3 nm, and 2.8 nm, respectively. The average particle size decreases with increasing cycle number. This may be because after the first cycle of Pd deposition, a significant number of hydroxyl groups are re-exposed, and Pd-H groups are generated and distributed on the titanate nanosurface. These sites facilitate the anchoring and dispersion of Pd particles in the next cycle. Another possible reason is that H2Ti3O7 shrinks at high temperatures, resulting in a large number of hydroxyl groups adsorbed on the surface.
[0058] Figure 5 and Figure 6 These are STEM and EDS mapping images of the 1cPd / H2Ti3O7 and 2cPd / H2Ti3O7 catalysts, where yellow represents Pd, green represents Ti, and blue represents O. This shows that Pd is uniformly and highly dispersed in the samples, indicating that Pd nanoparticles prepared using ALD technology have the advantage of high dispersion.
[0059] Example 2: This embodiment illustrates the application of the HBIW hydrodebenzylation catalyst in the primary HBIW hydrodebenzylation reaction. The catalyst used in this embodiment is the 1cPd / H2Ti3O7 HBIW hydrodebenzylation catalyst prepared in Example 1.
[0060] The specific process of the HBIW primary hydrodebenzylation reaction is as follows: 0.25 g HBIW, 20 mg catalyst, 0.63 mL N,N-dimethylformamide, 5 μL bromobenzene, and 0.375 mL acetic anhydride are sequentially added to a 100 mL high-pressure reactor. After sealing the reactor, it is purged three times with inert carrier gas nitrogen, then H2 is introduced and purged three more times. Finally, H2 is introduced to ensure that the pressure displayed on the reactor is at least 0.4 MPa, the rotation speed is 600 rpm, the first stage reaction temperature is 18 °C, and the reaction time is 7 hours. In the second stage, the temperature is increased to 20 °C and the reaction time is 16 hours. After filtration, washing, and drying, the yield of TADBIW is obtained after subtracting the amount of catalyst used. The reaction conditions and performance of HBIW primary hydrodebenzylation are listed in Table 2.
[0061] Example 3: This embodiment illustrates the application of the HBIW hydrodebenzylation catalyst in the primary HBIW hydrodebenzylation reaction. The catalyst used in this embodiment is the 1cPd / H2Ti3O7 HBIW hydrodebenzylation catalyst prepared in Example 1.
[0062] In this embodiment, the specific process of the HBIW primary hydrodebenzylation reaction is basically the same as in Example 2, except that in this embodiment, the temperature is increased to 25°C in the second stage. The HBIW primary hydrodebenzylation reaction conditions and performance are listed in Table 2.
[0063] Example 4: This embodiment illustrates the application of the HBIW hydrodebenzylation catalyst in the primary HBIW hydrodebenzylation reaction. The catalyst used in this embodiment is the 1cPd / H2Ti3O7 HBIW hydrodebenzylation catalyst prepared in Example 1.
[0064] In this embodiment, the specific process of the HBIW primary hydrodebenzylation reaction is basically the same as in Example 2, except that in this embodiment, the temperature is increased to 30°C in the second stage. The HBIW primary hydrodebenzylation reaction conditions and performance are listed in Table 2.
[0065] The recovered catalyst was designated as 1cPd / H2Ti3O7-spent-1, and ICP analysis showed that the Pd loading of the catalyst was 2.4 wt%.
[0066] Example 5: This embodiment illustrates the application of the HBIW hydrodebenzylation catalyst in the primary HBIW hydrodebenzylation reaction. The catalyst used in this embodiment is the 1cPd / H2Ti3O7 HBIW hydrodebenzylation catalyst prepared in Example 1.
[0067] In this embodiment, the specific process of the HBIW primary hydrodebenzylation reaction is basically the same as in Example 2, except that in this embodiment, the temperature is increased to 35°C in the second stage. The HBIW primary hydrodebenzylation reaction conditions and performance are listed in Table 2.
[0068] Example 6: This embodiment illustrates the application of the HBIW hydrodebenzylation catalyst in the primary HBIW hydrodebenzylation reaction. The catalyst used in this embodiment is the 1cPd / H2Ti3O7 HBIW hydrodebenzylation catalyst prepared in Example 1.
[0069] In this embodiment, the specific process of the HBIW primary hydrodebenzylation reaction is basically the same as in Example 2, except that in this embodiment, the temperature is increased to 40°C in the second stage. The HBIW primary hydrodebenzylation reaction conditions and performance are listed in Table 2.
[0070] Table 2 shows that the reaction temperature in the second stage of the HBIW primary hydrogenobenzyl dehydrogenation reaction affects the yield of the TADBIW product. The reaction rate decreases significantly at 20℃, while 40℃ leads to the decomposition of the substrate HBIW. Therefore, the optimal temperature window is 25-35℃.
[0071] Example 7: This embodiment illustrates the application of the HBIW hydrodebenzylation catalyst in the primary HBIW hydrodebenzylation reaction. The catalyst used in this embodiment is the 2cPd / H2Ti3O7 HBIW hydrodebenzylation catalyst prepared in Example 1.
[0072] In this embodiment, the specific process of the HBIW primary hydrodebenzylation reaction is basically the same as in Example 2, except that in this embodiment, the temperature is increased to 30°C in the second stage. The HBIW primary hydrodebenzylation reaction conditions and performance are listed in Table 2.
[0073] The recovered catalyst was designated as 2cPd / H-titanate-spent-1, and ICP analysis showed that the Pd loading of the catalyst was 4.1 wt%.
[0074] Example 8: This embodiment illustrates the application of the HBIW hydrodebenzylation catalyst in the primary HBIW hydrodebenzylation reaction. The catalyst used in this embodiment is the 3cPd / H2Ti3O7 HBIW hydrodebenzylation catalyst prepared in Example 1.
[0075] In this embodiment, the specific process of the HBIW primary hydrodebenzylation reaction is basically the same as in Example 2, except that in this embodiment, the temperature is increased to 30°C in the second stage. The HBIW primary hydrodebenzylation reaction conditions and performance are listed in Table 2.
[0076] The recovered catalyst was designated as 3cPd / H2Ti3O7-spent-1, and ICP analysis showed that the Pd loading of the catalyst was 7.5 wt%.
[0077] Examples 9-11: This example illustrates the application of HBIW hydrodebenzylation catalysts in the primary HBIW hydrodebenzylation reaction. The catalysts used in this example are the 1cPd / H2Ti3O7-spent-1, 2cPd / H2Ti3O7-spent-1, and 3cPd / H2Ti3O7-spent-1 catalysts from Examples 4, 7, and 8.
[0078] The specific process of the HBIW primary hydrogenodebenzylation reaction in this embodiment is as follows: 0.25g HBIW, 20mg catalyst, 0.63mL N,N-dimethylformamide, 5μL bromobenzene, and 0.375mL acetic anhydride were sequentially added to a 100ml high-pressure reactor. After sealing the reactor, it was purged three times with inert carrier gas nitrogen, then H2 was introduced and purged three more times, and finally H2 was introduced to ensure that the pressure displayed on the reactor was at least 0.4MPa. The rotation speed was 600rpm, the first stage reaction temperature was 18℃, and the reaction time was 7 hours. In the second stage, the temperature was increased to 30℃ and the reaction time was 16 hours. After filtration, washing, and drying, and after subtracting the amount of catalyst used, the final yields of TADBIW were 80.5%, 78.8%, and 78.4%, respectively. The reaction conditions and performance of the HBIW primary hydrogenodebenzylation reaction are listed in Table 2.
[0079] After the reaction was completed, the catalyst was recovered and designated as 1cPd / H2Ti3O7-spent-2, 2cPd / H2Ti3O7-spent-2, and 3cPd / H2Ti3O7-spent-2. The Pd loading of the catalyst was analyzed by ICP and found to be 2.1wt%, 3.8wt%, and 7.2wt%, respectively.
[0080] Examples 12-14: This embodiment illustrates the application of HBIW hydrodebenzylation catalysts in the primary HBIW hydrodebenzylation reaction. The catalysts used in this embodiment are the 1cPd / H2Ti3O7-spent-2, 2cPd / H2Ti3O7-spent-2, and 3cPd / H2Ti3O7-spent-2 catalysts from Examples 9-11.
[0081] The specific process of the HBIW primary hydrogen debenzylation reaction in this embodiment is as follows: 0.25g HBIW, 20mg catalyst, 0.63mL N,N-dimethylformamide, 5μL bromobenzene, and 0.375mL acetic anhydride were sequentially added to a 100ml high-pressure reactor. After sealing the reactor, it was purged three times with inert carrier gas nitrogen, then H2 was introduced and purged three more times, and finally H2 was introduced to ensure that the pressure displayed on the reactor was at least 0.4MPa. The rotation speed was 600rpm, the first stage reaction temperature was 18℃, and the reaction time was 7 hours. In the second stage, the temperature was increased to 30℃ and the reaction time was 16 hours. After filtration, washing, and drying, and after subtracting the amount of catalyst used, the final yields of TADBIW were 81.9%, 80.1%, and 80.8%, respectively. The reaction conditions and performance of the HBIW primary hydrogen debenzylation reaction are listed in Table 2.
[0082] The following formula was used to calculate the rate of decrease in TADBIW yield after three cycles of HBIW hydrogenobenzyl dehydrogenation catalyst recycling. ≤10%.
[0083] ; In the formula: This indicates the rate of decline in TADBIW yield; Indicates the initial yield; This indicates the third yield.
[0084] In this embodiment, the yield reduction rates of TADBIW after three uses of the 1cPd / H2Ti3O7, 2cPd / H2Ti3O7, and 3cPd / H2Ti3O7 catalysts were 6.0%, 6.9%, and 6.3%, respectively.
[0085] After the reaction was completed, the catalyst was recovered and designated as 1cPd / H2Ti3O7-spent-3, 2cPd / H2Ti3O7-spent-3, and 3cPd / H2Ti3O7-spent-3. The Pd loading of the catalyst was analyzed by ICP and found to be 2.0 wt%, 3.6 wt%, and 7.1 wt%, respectively.
[0086] Calculations show that after three cycles of 1cPd / H2Ti3O7, 2cPd / H2Ti3O7, and 3cPd / H2Ti3O7, the loss rates of the active material palladium are 20.0%, 16.3%, and 8.9%, respectively.
[0087] Comparative Example 1: This comparative example provides a method for preparing an HBIW hydrogen debenzylase catalyst, which includes the following steps: First, the catalyst support TiO2 (P25) is placed in a rotary reactor, the reactor is sealed, a vacuum is drawn to control the chamber pressure at 130 Pa, and the reactor is heated to 200 °C. The hexafluoroacetylacetone palladium precursor is preheated to 60 °C, and the inert carrier gas nitrogen flow rate is 100 ml / min. Then, the active material palladium is deposited on P25. One cycle of atomic layer deposition includes four steps: Step 1: Inject palladium hexafluoroacetylacetone precursor into the rotary reactor to induce an interfacial chemical reaction with P25. The injection time is 300 seconds.
[0088] Step 2: Purge with inert carrier gas nitrogen for 500 seconds.
[0089] Step 3: Inject formaldehyde precursor into the reactor to reduce the palladium hexafluoroacetylacetonate on the surface to generate palladium particles. The injection time is 600 seconds.
[0090] Step 4: Purge with inert carrier gas nitrogen for 500 seconds.
[0091] In this comparative example, the atomic layer deposition period of Pd is 1, and the catalyst is denoted as 1cPd / P25.
[0092] This comparative example also illustrates the application of the HBIW hydrodebenzyl catalyst in the HBIW primary hydrodebenzyl reaction. The catalyst used in this example is the 1cPd / P25 catalyst from Comparative Example 1.
[0093] The specific process of the HBIW hydrogenolysis reaction in this comparative example was as follows: 0.25 g HBIW, 20 mg catalyst, 0.63 mL N,N-dimethylformamide, 5 μL bromobenzene, and 0.375 mL acetic anhydride were sequentially added to a 100 mL high-pressure reactor. After sealing the reactor, it was purged three times with inert nitrogen carrier gas, followed by H2 and purging three more times. Finally, H2 was introduced to ensure the pressure displayed on the reactor was at least 0.4 MPa. The rotation speed was 600 rpm, the first stage reaction temperature was 18 °C, and the reaction lasted for 7 hours. In the second stage, the temperature was increased to 20 °C and the reaction lasted for 16 hours. After filtration, washing, and drying, the yield of TADBIW was obtained after subtracting the amount of catalyst used. The results are listed in Table 2. After the reaction was completed, the catalyst was recovered and designated as 1 cPd / P25-spent-1. After the catalyst was recycled for the second time, no TADBIW product was produced. Calculations show that after one cycle of 1cPd / P25, the loss rate of the active material palladium is 72.2%. The reaction conditions and performance of HBIW one-time hydrogen debenzylase reaction are listed in Table 2.
[0094] Comparative Example 2: This comparative example illustrates the application of an HBIW hydrodebenzyl catalyst in the primary HBIW hydrodebenzyl reaction. The catalyst used in this example is a commercially available 5 wt% Pd / C catalyst.
[0095] The specific process of the HBIW one-stage hydrogenodebenzyl reaction in this comparative example is as follows: 0.25 g HBIW, 20 mg catalyst, 0.63 mL N,N-dimethylformamide, 5 μL bromobenzene, and 0.375 mL acetic anhydride were sequentially added to a 100 mL high-pressure reactor. After sealing the reactor, it was purged three times with inert carrier gas nitrogen, then H2 was introduced and purged three more times, and finally H2 was introduced to ensure that the pressure displayed on the reactor was at least 0.4 MPa. The rotation speed was 600 rpm, the first stage reaction temperature was 18 °C, and the reaction lasted for 7 hours. In the second stage, the temperature was increased to 30 °C and the reaction lasted for 16 hours. After filtration, washing, and drying, the yield of TADBIW was obtained after subtracting the amount of catalyst used.
[0096] The catalyst after one cycle is designated as 5wt%Pd / C-spent-1, the catalyst after two cycles as 5wt%Pd / C-spent-2, and the catalyst after three cycles as 5wt%Pd / C-spent-3. After two cycles of the 5wt%Pd / C catalyst, no TADBIW product was observed. Calculations show that after three cycles of the 5wt%Pd / C catalyst, the loss rate of the active material palladium is 82%. The reaction conditions and performance of the HBIW primary hydrogenolysis benzyl dehydrogenation reaction are listed in Table 2.
[0097] The structures of commercially available 5 wt% Pd / C and Pd / H2Ti3O7 catalysts recovered after one cycle were characterized by XRD, and the results are as follows: Figure 7 As shown. The 1–3cPd / H₂Ti₃O₇ catalyst at 2θ = 9.3 0 24.5 0 28.7 0 48.6 0 A diffraction peak appeared at [location], corresponding to the diffraction peak of titanate nanotubes; no diffraction peak was observed for Pd. After one use, the 5 wt% Pd / C catalyst [value] at 40.6 [units of measurement missing]. 0 46.6 0 67.8 0 81.7 0 The presence of diffraction peaks at the positions corresponding to the (111), (200), (220), and (311) crystal planes of Pd indicates that Pd aggregates into large particles after one use of the commercial 5% Pd / C catalyst. These results fully demonstrate that the confinement effect of the H2Ti3O7 support and the strong interaction between Pd and O-Ti effectively inhibit Pd aggregation.
[0098] The catalyst recovered after one cycle was characterized using TEM, such as... Figure 8 As shown. From Figure 8 As shown in 'a', after one cycle, the Pd particles in the commercial 5wt% Pd / C catalyst exhibited significant agglomeration and increased size. This is consistent with... Figure 7 The XRD results were consistent. After one cycle, the Pd particle size of the 1–3 cPd / H2Ti3O7 catalyst did not change significantly, the particle size distribution was concentrated, and there was no obvious agglomeration or enlargement of Pd particles.
[0099] Figure 9 This indicates that Pd particles also showed significant aggregation on the P25 support, demonstrating that the confinement effect effectively anchored the Pd particles and prevented them from migrating.
[0100] The electronic structures of commercially available 5 wt% Pd / C and Pd / H₂Ti₃O₇ catalysts recovered after one cycle were characterized using XPS, such as... Figure 10 As shown. From Figure 10The a-c values show that the Pd3d binding energy is between 335.1 and 335.4 eV. 0 The increased peak area ratio may be due to the reduction of PdO to Pd in an H2 atmosphere. 0 .
[0101] Table 2 HBIW One-Time Hydrogen Debenzylation Reaction Conditions and Performance
Claims
1. An HBIW hydrogenolysis benzyl catalyst, characterized in that, The catalyst uses titanate nanotubes as a support, on which palladium is loaded as an active material. The palladium is a nanoparticle with an average particle size of 1 to 5 nm, and the loading of palladium is 2.5 wt% to 7.8 wt%.
2. A method for preparing the HBIW hydrogenobenzyl dehydrogenase catalyst as described in claim 1, characterized in that, This method involves synthesizing a palladium catalyst supported on titanate nanotubes using atomic layer deposition in a rotary reactor, with palladium hexafluoroacetylacetone as a carrier and formaldehyde as a precursor. The palladium catalyst supported on titanate nanotubes is the HBIW hydrogen debenzylase catalyst.
3. The preparation method of the HBIW hydrogenobenzyl dehydrogenase catalyst as described in claim 2, characterized in that, The method involves evacuating the rotary reactor to control the chamber pressure at 100–200 Pa, heating the rotary reactor to 150–200 °C, preheating the palladium hexafluoroacetylacetone precursor to 50–60 °C, and using an inert carrier gas flow rate of 100–200 ml / min. Then, the active material palladium is deposited on titanate nanotubes for 1–3 cycles using atomic layer deposition.
4. The preparation method of the HBIW hydrogenolytic benzyl catalyst as described in claim 3, characterized in that, The method involves evacuating the rotary reactor to control the chamber pressure at 130 Pa, heating the rotary reactor to 200 °C, preheating the palladium hexafluoroacetylacetone precursor to 60 °C, and using an inert carrier gas flow rate of 100 ml / min.
5. The preparation method of the HBIW hydrogenobenzyl dehydrogenase catalyst as described in claim 2, characterized in that, One cycle of the atomic layer deposition method described above includes the following four steps: Step 1: Inject palladium hexafluoroacetylacetonate precursor to induce an interfacial chemical reaction with titanate nanotubes. The injection time of palladium hexafluoroacetylacetonate precursor is 100-2000 seconds. Step 2: Purge with inert carrier gas for 200–1000 seconds; Step 3: Inject palladium hexafluoroacetylacetonate onto the surface of the formaldehyde precursor. The formaldehyde precursor injection time is 150–3000 seconds. Step 4: Purge with inert carrier gas for 200-1000 seconds.
6. The application of the HBIW hydrodebenzylation catalyst as described in claim 1 in the primary HBIW hydrodebenzylation reaction; the rate of decrease in TADBIW yield after the HBIW hydrodebenzylation catalyst is recycled 3 times. ≤10%, loss rate of active material palladium ≤20wt.
7. The application as described in claim 6, characterized in that, The decrease in TADBIW yield after the HBIW hydrogenolysis benzyl catalyst was recycled three times. ≤6.9%, loss rate of active material palladium ≤9wt%.
8. The application as described in claim 6, characterized in that, The amount of palladium, the active material, in the titanate nanotube-supported sub-nanometer palladium catalyst is 5.0 wt‰ to 15.6 wt‰ of the hexabenzylhexaazaisowulzane.
9. The application as described in claim 6, characterized in that, The reaction temperature for the HBIW primary hydrogen debenzylation reaction is 20℃~40℃.
10. The application as described in claim 6, characterized in that, The yield of the TADBIW was 80.4% to 87.2%.